A hybrid entity structure for tax optimization of foreign direct investment in the U.S. - Thomas Kollruss (Journal of Corporate Accounting & Finance, 2023)
This article develops a new strategy for the (tax) optimization of foreign direct investments in the U.S. This strategy is particularly favorable for natural persons. By using a foreign upstream hybrid partnership, a substantial tax optimization of the current taxation of profits as well as the taxation of capital gains can be achieved. In addition, current and final losses may also be offset cross-border to a certain extent in the case of an exemption under treaty law. This tax structuring idea is presented by way of example and explained on the basis of the country constellation U.S./Germany.
Keywords: 650; corporate structure; finance; international taxation; strategy; tax optimization